FROM RURAL GRAZING AREA (RUGA) TO NATIONAL LIVESTOCK TRANSFORMATION PLAN (NLTP): A MERE CHANGE OF NAME OR REINCARNATION (LAPAI JOURNAL OF NIGERIA HISTORY, 2024)
Political and social instability in numerous African countries has exacerbated conflicts, particularly between farmers and herders, driven by resource competition and environmental degradation. In Nigeria, the escalation of farmer-herder conflict has led to widespread displacement, increased food prices and security challenges. Government interventions such as the Rural Grazing Area (RUGA) and National Livestock Transformation Plan (NLTP) policieshave faced scrutiny, prompting a comparative analysis to evaluate their effectiveness and public reception. This study examines the RUGA policy and its alternative, the NLTP, in Nigeria using historical methodology and secondary data, including interviews and national newspapers. RUGA policy was introduced in 2018 to mitigate farmer-herder conflicts; the policy encountered significant opposition due to perceived socio-political implications and a lack of stakeholder consultation. It is argued that it favoured the Fulani ethnic group and could exacerbate ethnic tensions, eliciting mixed public reactions. In contrast, the NLTP aimed to modernise livestock management and enhance productivity through a phased transition from open grazing to ranching. Despite its comprehensive approach focusing on stakeholder engagement, conflict resolution, humanitarian relief and economic development, the NLTP also faced scepticism, with some perceiving it as a rebranded RUGA policy. Findings from the study underscored thesignificant public debate and resistance both policies generated and emphasised the complexities of addressing farmer-herder conflicts in Nigeria. The study concludes that inclusiveness of stakeholder engagement, transparent communication, and addressing underlying socio-political concerns are necessary. It advocates for a balanced approach to promote sustainable livestock management practices across ethnic groups.